Influence of the Brønsted acidity, SiO2/Al2O3 ratio and Rh-Pd content on the ring opening. Part II. Selective ring opening of methylcyclohexane - D'ippolito, Silvana Andrea (2014)
Monometallic and bimetallic Pd-Rh catalysts with various Rh/Pd atomic ratios (=0.5, 1 and 2) and a total metal charge of 1 wt% supported on SiO2-Al2O3(SIRAL 40, 20, 5) were studied for the ring opening of methylcyclohexane (MCH). The results were compared with those obtained previously for ring opening of decalin. It was found that the total acidity and the Brønsted acidity of the support have a higher influence on the activity for ring opening of naphthenic bicycles than on the activity for opening single rings. The influence of the metal charge is more important on the reaction of MCH. All the catalysts display a high MCH conversion, which increases with the reaction temperature. The bimetallic catalyst with the Rh/Pdratio equal to 2 and supported on SIRAL 40 has the highest yield to ring opening products.